IMPLEMENTASI PROGRAM BEDAH RUMAH DALAM PENINGKATAN TARAF HIDUP WARGA MISKIN DI DESA CANGGU - Maulida, Fahira; Prabawati, Ni Putu Anik; Yasintha, Putu Nomy (CITIZEN CHARTER, 2020)
ABSTRACTl The House Renovation Program is a public policy implemented in the Canggu Village of Badung Regency, the purpose of which is to provide a decent house for poor people who have a house unfit for habitation. This research uses descriptive qualitative research methods with data collection techniques such as observation, interviews and documentation. Indicators used of this study are (1) standards and policy objectives, (2) resources, (3) characteristics of implementing agents, (4) attitude of aimplementers, (5) Communication limplementers, (6) lsocial, economicl environment and politics. Thel results ofl the research from this Program show that the implementation of this program has been carried out well, but not completely. Whereas for resources there are problems in the budget or funds provided, then the attitude of the implementer and the social, economic and political environment there are obstacles in the understanding of the community towards the implementation phase of this program is lacking. Keywords : Policy Implementation, House Renovation Program, Standard Of Living, Canggu Village